STRATEGY TO ENHANCE THE COMPETITIVENESS OF COFFEE BEAN EXPORTERS IN NORTH SUMATRA - Cindy Sakhila; Fahmi Natigor Nasution; Wahyu Ario Pratomo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to formulate strategies to enhance the competitiveness of coffee bean exporters in North Sumatra in facing global market dynamics. Considering North Sumatra's strategic role as one of Indonesia's leading producers of high-quality Arabica coffee, this research focuses on four key factors affecting competitiveness, namely product quality, production costs, pricing, and international trade policies. The research employs a mixed-method approach with case studies involving five coffee export companies: PT. Ujang Jaya International, PT. Tibeka Jaya Abadi, PT. Arvis Sanada Sanni Indonesia, PT. Mulya Sari Mandiri, and PT. Indokom Citra Persada. Data collection was conducted through in-depth interviews, observations, document studies, and questionnaire distribution. Qualitative data were analyzed using the SOAR (Strengths, Opportunities, Aspirations, Results) framework, while quantitative data were analyzed using the Analytical Hierarchy Process (AHP) method to determine strategic priorities. The findings indicate that enhancing product quality through international certifications and cupping tests, improving production cost efficiency through modern sorting processes and direct farmer partnerships, as well as optimizing government export promotion policies are key factors in strengthening the competitiveness of North Sumatra's coffee bean exports. These findings are expected to provide practical contributions for exporters, policymakers, and the development of academic literature in agricultural export management.